The effect of different borehole spacing and detonation time difference on crack propagation in double-hole shaped charge blasting - Shixiang Xu; Bo Wu; Zhongsi Dou (PLoS ONE, 2026)
Achieving precise through-crack between shaped charge blasting holes depends critically on the design parameters of the blasting operation. This study investigated the influence of borehole spacing and detonation time difference on crack propagation in shaped charge blasting using LS-DYNA numerical simulation. The reliability of the numerical model was verified through experiment test, and a double-hole shaped charge blasting calculation model was established. The dynamic evolution law of crack in double-hole shaped charge blasting under different borehole spacing and detonation time difference was analyzed. The results indicate that increasing borehose spacing leads to more severe stress wave attenuation, significantly reducing the peak effective stress at the center point between holes. Micro-delayed detonation regulates the stress field through timing control, thereby altering crack propagation behavior. As the delay time increases, crack originating from the first detonated hole account for a larger proportion of the propagation path, and the crack connection point shifts toward the later-detonated hole. Optimizing borehole spacing and micro-delay detonation can effectively promote inter-hole crack propagation. This study provides a theoretical basis for designing shaped charge blasting parameters in mining operations, tunnel excavation, and other engineering applications.